Study of inhalation micropowders obtained by spray drying - L. A. Shcherbakova; A. I. Saitgareeva; M. G. Gordienko; R. R. Safarov (Тонкие химические технологии, 2024)
Objectives. To study the influence of the type of matrix-forming material and excipients concentration, spray drying parameters on the characteristics of the powder for inhalation, as well as to investigate the inhalation compositions for stability under stressful conditions.Methods. Spray drying was used to obtain powder compositions with the required characteristics for inhalation therapy. Microscopic and analytical studies of powders were carried out. Statistical analysis made it possible to estimate the influence of factors on the powder characteristics and rank them by importance. The stability of spray dried powders was studied.Results. The optimal parameters for obtaining powders for inhalation were found by means of mathematical statistics: air flow rate was 37 m3/h; compressed air flow rate — 601 L/h; inlet air temperature — 150°C; solution flow rate — 45% of the power of the peristaltic pump (16.3 g/min for this composition); L-leucine concentration — 10 wt %; ratio of components of the matrix polyvinylpyrrolidone K-30/D-mannitol = 1 : 3. Under these conditions, as well as by means of 2 experiments additionally selected from the research design, a composition with isoniazid as an active substance was spray dried. The resulting powders were analyzed, in order to confirm the correctness of the recommended parameters.Conclusions. The selection of compositions and spray drying conditions involves multiple criteria. The characteristics of the powder for inhalation may deteriorate significantly during long-term storage. The optimal parameters were determined using statistical analysis and confirmed by experimental data.